2020
DOI: 10.18070/erciyesiibd.659335
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Economic Factors and Health Personnel Employment in Turkey: An Econometric Anaylsis

Abstract: This study applies the ARDL (Autoregressive Distributed Lag) bounds testing approach developed by Pesaran, Shin and Smith (2001) to reveal the relationship between economic factors and health personnel employment in Turkey between 1974-2015. While the health personnel data includes the number of physicians and other health personnel (midwives and nurses), reel GDP (Real Gross Domestic Product) and economic crises are included as economic factors in the study. In terms of long-run relationships between economic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
1
0
0
1
Order By: Relevance
“…Findings obtained in the study were reported by Şimşek and Kadılar (2008), Yapraklı and Yurttançıkmaz (2010), Ogbonna (2014), Dehghani et al (2015), Altunöz (2017), Kofoğlu (2018), Atgür (2021).…”
Section: Discussionsupporting
confidence: 66%
“…Findings obtained in the study were reported by Şimşek and Kadılar (2008), Yapraklı and Yurttançıkmaz (2010), Ogbonna (2014), Dehghani et al (2015), Altunöz (2017), Kofoğlu (2018), Atgür (2021).…”
Section: Discussionsupporting
confidence: 66%
“…Uygulama sürecinde öncelikle uygun gecikme uzunluğunun belirlenmesi gerekmektedir. Bu amaçla Akaike Bilgi Kriteri (AIC) çerçevesinde maksimum gecikme sayısı literatürde yıllık veriler için sıklıkla kullanılan 4 değeri olarak alınmış (Çıraklı, 2019;Terzi ve Bekar, 2019) ARDL modeli ile geçerli ve güvenilir kısa-uzun dönem sonuçların üretilebilmesi için uygun modelin belli varsayımları yerine getirmesi gerekmektedir. Bunlardan ilk hata terimlerinin normal dağılıma uygunluğudur ve Jarque-Bera istatistiği sonuçları varsayımın sağlandığını göstermektedir.…”
Section: Ardl Testi Sonuçlarıunclassified